2020
DOI: 10.1186/s12992-020-00619-7
|View full text |Cite
|
Sign up to set email alerts
|

Equity and elderly health in India: reflections from 75th round National Sample Survey, 2017–18, amidst the COVID-19 pandemic

Abstract: Background Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) outbreak, called coronavirus disease - 2019 (COVID-19), has affected more than 200 countries across the globe with a higher fatality rate among the elderly population. Aim of the study is to highlight the vulnerability of the aged amidst the current COVID-19 pandemic, and in the light of the recent international evidence, suggests what government could do to mitigate their vulnerability. Methods Data from the recently released (November … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
5
26
0
1
Order By: Relevance
“…Our study confirmed that the elderly living in urban residence and elderly males have shown higher hospitalization rate where these findings were consistent with previous research 11,17,[32][33][34][35]38 . Our results revealed that elderly women have lower odds of hospitalization than the elderly men and similar patterns of hospitalizations were also observed in other countries like-England 39 , Norway 17,40 , Italy 41 , but countries like Denmark 42 , Finnland 40 , South Korea 43 and Brazil 44 have shown higher hospitalization among older women than older men.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study confirmed that the elderly living in urban residence and elderly males have shown higher hospitalization rate where these findings were consistent with previous research 11,17,[32][33][34][35]38 . Our results revealed that elderly women have lower odds of hospitalization than the elderly men and similar patterns of hospitalizations were also observed in other countries like-England 39 , Norway 17,40 , Italy 41 , but countries like Denmark 42 , Finnland 40 , South Korea 43 and Brazil 44 have shown higher hospitalization among older women than older men.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that elderly women have lower odds of hospitalization than the elderly men and similar patterns of hospitalizations were also observed in other countries like-England 39 , Norway 17,40 , Italy 41 , but countries like Denmark 42 , Finnland 40 , South Korea 43 and Brazil 44 have shown higher hospitalization among older women than older men. Interestingly, our study have showed that married elderly was found to be less likely to be hospitalized than unmarried, these finding are analogous to the other previous studies 11,35,[45][46][47][48] . Our study also confirmed that elderly living alone are more likely to be hospitalized than living with spouse or other than spouse and were also documented in other studies 35,[49][50][51][52][53] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of this study are in tune with previous studies on health inequities [ 5 , 26 , 27 , 50 – 53 ] pertaining to both developed and developing countries that have affirmed the applicability of the social gradient hypothesis with findings suggesting that the level of health care utilisation is distributed along the social gradients. A number of studies have provided evidence that a person with lower level of educational attainment and income is less likely to have access to health care services and vice versa [ 54 – 56 ]. The present study confirms the same.…”
Section: Discussionmentioning
confidence: 99%